CPC-093 Nosocomial Infections in a Cohort of Extra-Corporeal Life Support Patients. (12th March 2013) - Lenehan, D; Scanlon, N; Conrick-Martin, I; O'Gorman, J; Oshodi, D; O'Brien, S; Hannan, M; Lynch, M; Carton, E; Meegan, C
Abstract : Background: Extra-Corporeal Life Support (ECLS) is a method of life support used to treat patients with severe respiratory and/or cardiac failure refractory to conventional modes of treatment. Nosocomial infections in these patients are associated with increased morbidity and mortality along with increased lengths of intensive care unit (ICU) and hospital stay. No international best-practise consensus guidelines exist for treatment and/or prophylaxis of infections in this patient group. Purpose: To examine the rate of nosocomial infection in MMUH ECLS patients as well as the consumption of antimicrobials in the treatment and prevention of these infections. Materials and Methods: In a retrospective cohort study, the pharmacy records from a daily multi-disciplinary microbiology round reviewed all patients who are on ECLS. The use of prophylactic and therapeutic antimicrobials in these patients was assessed as well as the background ICU bloodstream infection rate. Results: Data analysis yielded a total of 17 patients over a two-year period, with a total of 444 ECLS days. In total, there were 17 infections in this cohort including 4 (24%) blood-stream infections (yielding a rate of 9.0 per 1000 ECLS days). The first four ECLS patients received antibacterial (vancomycin) and antifungal (caspofungin) prophylaxis for the duration of ECLS, whereas the later cohort of 13 did not. In the cohort of patients who received prophylactic antimicrobials, defined daily doses (DDDs) per 100 ECLS days for vancomycin and meropenem were 49.54 and 49.63 respectively. For the non-prophylaxis cohort this was 25.31 and 37.73 respectively. Conclusions: The infection rate in this cohort was low. In particular, the bloodstream infection rate compared favourably with previously published rates, and was comparable with the 'background' bloodstream infection rate of the ICU population as a whole. Antimicrobial use in ECLS patients was high relative to overall ICU antimicrobial use. No conflict of interest.